Hybrid precoding in point-to-point massive multiple-input multiple-output systems based on normalised matrix adaptive method - Feng, Yongpan; Kim, Suk Chan (IET communications, 2017)
The potential of millimetre wave frequencies band has motivated the study of large-scale antenna arrays to improve the spectrum efficiency of massive multiple-input multiple-output wireless communications systems. However, conventional fully digital precoding schemes, which require one radio frequency (RF) chain for each antenna, are cost prohibitive and have high-power consumption. To address these hardware limitations, this study considers a hybrid precoding scheme that provides high performance in terms of spectrum efficiency. By deducing the derivative of the spectrum efficiency function with respect to the phase matrix variable of the RF precoder, an efficient RF precoding scheme based on the normalised matrix adaptive method (NMAM) is proposed. Numerical simulations show that the NMAM achieves excellent performance approaching that of fully digital precoding, with relatively low computational complexity.